APLIKASI MANAJEMEN DALAM AKTIFITAS DAKWAH - M. Sabir (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
In reality, da'wah is an effort to actualize Islamic values and teaching in Muslim's life which include personal, family and society, in order that the best Muslim community can be established. The management of da'wah means a process of spreading Islamic da'wah carried out either by individuals or groups-organisations and institutions-by taking such systematic steps as setting goal and form of activity to achieve the goal of da'wah in an effective and optimal way. In addition to human elements, there are still other elements in management such as money, materials, machine, methods, and market. In management process, money is the most important element since no activity can run well without financial support.